2017
DOI: 10.3390/molecules22071237
|View full text |Cite
|
Sign up to set email alerts
|

A Novel and Practical Chromatographic “Fingerprint-ROC-SVM” Strategy Applied to Quality Analysis of Traditional Chinese Medicine Injections: Using KuDieZi Injection as a Case Study

Abstract: Fingerprinting is widely and commonly used in the quality control of traditional Chinese medicine (TCM) injections. However, current studies informed that the fingerprint similarity evaluation was less sensitive and easily generated false positive results. For this reason, a novel and practical chromatographic “Fingerprint-ROC-SVM” strategy was established by using KuDieZi (KDZ) injection as a case study in the present article. Firstly, the chromatographic fingerprints of KDZ injection were obtained by UPLC an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…HPLC fingerprint has become the most widely used method due to its high reproducibility and sensitivity [ 3 ]. The HPLC fingerprint method applied to QE of HMs is mainly based on the similarity of fingerprints and the presence or absence of chromatographic peaks among samples [ 4 , 5 ]; however, this method cannot identify what these peaks are. Q-TOF-MS/MS is a kind of tandem mass spectrometry providing a high mass resolution and accurate mass measurement for the structural elucidation of unknown chemicals [ 6 ] and can be used in the identification of common peaks in HPLC fingerprints.…”
Section: Introductionmentioning
confidence: 99%
“…HPLC fingerprint has become the most widely used method due to its high reproducibility and sensitivity [ 3 ]. The HPLC fingerprint method applied to QE of HMs is mainly based on the similarity of fingerprints and the presence or absence of chromatographic peaks among samples [ 4 , 5 ]; however, this method cannot identify what these peaks are. Q-TOF-MS/MS is a kind of tandem mass spectrometry providing a high mass resolution and accurate mass measurement for the structural elucidation of unknown chemicals [ 6 ] and can be used in the identification of common peaks in HPLC fingerprints.…”
Section: Introductionmentioning
confidence: 99%
“…Quality assessment of Chinese medicines (CMs) is an important issue in the modernization of traditional Chinese medicine (TCM), for CMs have been widely applied in clinical therapy in China and other developing countries [ 1 , 2 ]. Various analytical methods have been adopted to ensure the quality of CM products by measuring the concentration of major chemical ingredients by high performance liquid chromatography (HPLC), gas chromatography (GC), liquid chromatography-mass spectrometry (LC-MS), near-infrared spectroscopy (NIRS), and so on [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The similarities of all 18 batches of R. tanguticum were >0.8 except two batches <0.8 and >0.7, of which three batches exceeded 0.9 (shown in Table 1). The similarity of fingerprints is generally used to evaluate the quality of an HM (Yang et al, 2017). The results indicated that there were certain quality differences between the three species of rhubarb; the quality of R. tanguticum was relatively good.…”
Section: Resultsmentioning
confidence: 99%
“…The similarity of fingerprints is generally used to evaluate the quality of an HM (Yang et al, 2017). The results indicated that there were certain quality differences between the three species of rhubarb; the quality of R. tanguticum was relatively good.…”
Section: Establishment Of the Hplc Fingerprint And Similarity Analysismentioning
confidence: 99%